PENGEMBANGAN KOMPETENSI APARATUR DALAM PERSPEKTIF PENGELOLAAN DAN PELAYANAN UMUM DI KANTOR DESA - Shokib .; Sugeng Rusmiwari (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Abstract: It was considered that government could not actualize the people welfare and it was not optimal yet. One of the causes was the government that was not competence in doing their duty. The result of this research was describing and knowing about the barrier factors in developing government competension, managerial perspective and public service at Pandanrejo village.The research method used qualitative research. The data sources were primary and secondary data. The data collecting were observation, interview and documentation. The sampling taking model was purposive sampling. The informants were the head of village, the secretary of village, the head of government bussines, the head of government financial also the head of public bussines. Next, the data were analyzed by reduce the data, data presentation and verification. The triangulasi technique was used to prove the validation of data. The result of the research shoerd that the village government of Pandanrejo did the internal competension in developing also excursion study or even workshop oftenly delegated their government to follow the training and technique preparation (Bimtek). Problems in developing the competence of government itself. Key-words: Development, Competence, Service. Abstrak: Pemerintah dalam mewujudkan kesejahteraan masyarakat, melalui pelayanan publik masih kurang optimal. Salah satu penyebabnya adalah aparatur yang kurang berkompeten dalam menjalankan tugasnya. Tujuan penelitian untuk mendiskripsikan dan mengetahui faktor-faktor penghambat pengembangan kompetensi aparatur perspektif pengelolaan dan pelayanan umum di Desa Pandanrejo. Metode penelitian menggunakan Jenis penelitian kualitatif, dengan sumber: data primer dan sekunder. Kemudian teknik pengumpulan data: observasi, wawancara dan dokumentasi sedangkan teknik penentuan informan yaitu purposive sampling. Informanya adalah Kepala Desa, Sekretaris Desa, Kaur Pemerintahan, Kaur keuangan dan Kaur umum. Selanjutnya data dianalisis dengan reduksi data, penyajian data dan verifikasi. Untuk menguji keabsahan data menggunakan triangulasi teknik. Hasil penelitian menunjukan bahwa, Pemerintah Desa Pandanrejo dalam pengembangan kompetensi yaitu selain di internal ada studi banding atau workshop juga mendelegasikan aparaturnya untuk mengikuti pembinaan dan bimbingan teknis (Bimtek). Hambatan diantarannya, SDM yang sudah tua dan terbatasnya alokasi dana untuk pengembangan kompetensi aparatur tersebut. Kata Kunci: Pengembangan, Kompetensi, Pelayanan